Deuteron structure in the deep inelastic regime - García Canal, Carlos Alberto (2017)
We study nuclear effects in the deuteron in the deep inelastic regime using the newest available data. We put special emphasis on their Q2 dependence. The study is carried out using a scheme which parameterizes, in a simple manner, these effects by changing the proton and neutron stucture functions in medium. The result of our analysis is compared with other recent proposals. We conclude that precise EMC ratios cannot be obtained without considering the nuclear effects in the deuteron